The Influence of Service Quality on Outpatient Satisfaction of National Health Insurance Participants Who Are Not Beneficiaries of Contribution Assistance at Sultan Sulaiman Regional Hospital - Lubis, Ika Syani Putri (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2025)
ABSTRACT Background: In the era of National Health Insurance, hospitals must improve their services for patient satisfaction and increase access to health services. National Health Insurance patients have been treated at one of the government-owned hospitals, Sultan Sulaiman Regional General Hospital, Serdang Bedagai Regency. The number of outpatient visits for National Health Insurance participants who are Non-Recipients of Contribution Assistance (Non-PBI) at Sultan Sulaiman Regional General Hospital has decreased by 31.4% over the past two years, namely 2014 and 2015. Objective: The purpose of this study was to evaluate the effect of service quality on the satisfaction of National Health Insurance participant outpatients at Regional public hospital Sultan Sulaiman. Method: The research method was an explanatory survey. This study involved 243 non-PBI National Health Insurance participant outpatients, and 71 samples were taken by chance. The data, collected through questionnaire interviews, were analyzed using multiple linear regression tests with α = 0.05. Results: The results showed that the satisfaction of non-PBI National Health Insurance participant outpatients at Regional public hospital Sultan Sulaiman was statistically influenced by the quality of doctor services, which included aspects of physical evidence, reliability, and responsiveness.